2022
DOI: 10.1039/d2me00071g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photoswitchable organometallic complexes with azobenzene and stilbene units: the case of Au(i)

Abstract: Two families of hetero- and homoleptic mononuclear Au(I) complexes with alkynyl ligands containing azo (XN) or stilbene (XC) group have been prepared and characterized by spectroscopic methods and single crystal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…15–20 Nevertheless, functionalisation of the phenyl rings of these derivatives with different donor groups has also been conducted, with the aim of having a photoactive dangling azo moiety coordinatively attached to a transition metal. 21–27 The possible implication of these appended photoswitches in biologically relevant interactions has also been reported. 28,29 Furthermore, the incorporation of derivatives having both phenyl rings modified with suitable donors has also been explored for its inclusion in transition metal 2D and 3D frameworks.…”
Section: Introductionmentioning
confidence: 98%
“…15–20 Nevertheless, functionalisation of the phenyl rings of these derivatives with different donor groups has also been conducted, with the aim of having a photoactive dangling azo moiety coordinatively attached to a transition metal. 21–27 The possible implication of these appended photoswitches in biologically relevant interactions has also been reported. 28,29 Furthermore, the incorporation of derivatives having both phenyl rings modified with suitable donors has also been explored for its inclusion in transition metal 2D and 3D frameworks.…”
Section: Introductionmentioning
confidence: 98%
“…21−23 Recently, the combination of organometallics and azo moiety in the same system has attracted tremendous attention in the area of organometallic chemistry, which provides the possibility of superposed properties of the metal center and photochromic "ON− OFF". 24,25 In a previous study, Chen et al synthesized a series of azo-containing phthalocyanines which showed very large second hyperpolarizability (γ) at the order of 10 −30 esu (1a.u. .…”
Section: Introductionmentioning
confidence: 99%
“…The azo functional group can be introduced into almost any organic skeleton to construct a more extended π-conjugated system and produce unusual photochromic behavior . Organometallic complexes as a significant branch of organic NLO materials deliver more appealing properties in low-energy d–d excitation and additional metal-to-ligand charge transfer (MLCT), ligand-to-metal charge transfer (LMCT), or ligand-to-ligand charge transfer (LLCT). Recently, the combination of organometallics and azo moiety in the same system has attracted tremendous attention in the area of organometallic chemistry, which provides the possibility of superposed properties of the metal center and photochromic “ON–OFF”. , In a previous study, Chen et al synthesized a series of azo-containing phthalocyanines which showed very large second hyperpolarizability (γ) at the order of 10 –30 esu (1a.u. = 5.0 × 10 –40 esu) .…”
Section: Introductionmentioning
confidence: 99%